2016
DOI: 10.1039/c6fd00007j
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fluoride ions on the equilibrium between titanium ions and titanium metal in fused alkali chloride melts

Abstract: KF is employed as a source of fluoride ions added to the melt to disclose the influence of fluoride on the disproportionation reactions of titanium ions, 3Ti(2+) = 2Ti(3+) + Ti, and 4Ti(3+) = 3Ti(4+) + Ti. The results reveal that the equilibrium transferred to the right direction for the first reaction and the apparent equilibrium constant increased sharply, mainly because of the formation of coordination compounds: TiFi(3-i). The accurate values of the equilibrium constants referring to the formation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…(6) and (7) were ¹0.12 and ¹0.46 V, respectively. 22 This may well explain why the potential of Eq. (6) was lower than that of Eq.…”
Section: àmentioning
confidence: 97%
See 1 more Smart Citation
“…(6) and (7) were ¹0.12 and ¹0.46 V, respectively. 22 This may well explain why the potential of Eq. (6) was lower than that of Eq.…”
Section: àmentioning
confidence: 97%
“…22 Therefore, NaF likely reacted with TiCl 4 to form Na 2 TiF 6 and Na 2 TiF 6 was decomposed to Na + and ½TiF 6 2À in the melts.…”
Section: 21mentioning
confidence: 99%
“…In comparison to other molten salt electrolytes systems, the electrochemical behaviour of titanium ions in chloride melts is different because of the stability of various oxidation states of titanium ions, which is caused by the influence of electrolyte composition [12][13][14][15] and temperature [14,15].…”
Section: Introductionmentioning
confidence: 97%
“…The fundamental aspects of chemistry and electrochemistry of titanium ions in molten salt electrolytes have been investigated, but data on the electrochemical behaviour of titanium ions in molten chloride/fluoride salt electrolytes are scarce and contradictory. The main barrier for successful development of an electrochemical route for aluminium-titanium alloy production is associated with the existence of different oxidation states of dissolved titanium species, namely Ti(II), Ti(III) and Ti(IV) [9,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the cathodic process of TiO 2 could be inuenced by the composition of the electrolyte and the cathode metal activity. The published literature has reported that the cathodic process of Ti(III) ions will change from a two-step reduction (Ti 3+ + e À ¼ Ti 2+ and Ti 2+ + 2e À ¼ Ti) to a one-step reduction (Ti 3+ + 3e À ¼ Ti) with an increase in uoride ion concentration in molten chloride 23,24 and the underpotential deposition of Ti(III) ions will occur at an active cathode, including liquid metal cathodes. 25 Therefore, this work investigates the feasibility of the direct electrochemical preparation of Ti-Fe alloys by MOE at a liquid iron cathode in a CaO-Al 2 O 3 -MgO-TiO 2 melt.…”
Section: Introductionmentioning
confidence: 99%